SAGER: a database of Symbiodiniaceae and Algal Genomic Resource. (4th July 2020) - Yu, Liying; Li, Tangcheng; Li, Ling; Lin, Xin; Li, Hongfei; Liu, Chichi; Guo, Chentao; Lin, Senjie
Abstract: Symbiodiniaceae dinoflagellates are essential endosymbionts of reef building corals and some other invertebrates. Information of their genome structure and function is critical for understanding coral symbiosis and bleaching. With the rapid development of sequencing technology, genome draft assemblies of several Symbiodiniaceae species and diverse marine algal genomes have become publicly available but spread in multiple separate locations. Here, we present a S ymbiodiniaceae and A lgal Ge nomic R esource Database (SAGER), a user-friendly online repository for integrating existing genomic data of Symbiodiniaceae species and diverse marine algal gene sets from MMETSP and PhyloDB databases. Relevant algal data are included to facilitate comparative analyses. The database is freely accessible at http://sampgr.org.cn . It provides comprehensive tools for studying gene function, expression and comparative genomics, including search tools to identify gene information from Symbiodiniaceae species, and BLAST tool to find orthologs from marine algae and protists. Moreover, SAGER integrates transcriptome datasets derived from diverse culture conditions of corresponding Symbiodiniaceae species. SAGER was developed with the capacity to incorporate future Symbiodiniaceae and algal genome and transcriptome data, and will serve as an open-access and sustained platform providing genomic and molecular tools that can be conveniently used to study Symbiodiniaceae and other marine algae. Database URL: http://sampgr.org.cn